A previously cryptic diguanylate cyclase can be active and allows Bdellovibrio bacteriovorus to become a selective predator on human pathogens - Al-Bayati, Asmaa Mohammed Sulaiman (2017)
Bdellovibrio bacteriovorus is a small deltaproteobacterium which invades, grows and replicates rapidly inside the periplasm of other Gram-negative bacteria including human pathogens in a Host-dependent (HD) manner. Cyclic-di-GMP is a second bacterial messenger that controls complex processes in bacteria. Pioneering previous work deduced that Bdellovibrio bacteriovorus have four diguanylyl cyclases (Dgcs) responsible for c-di-GMP synthesis and certain diguanylyl cyclases have discrete roles in Bdellovibrio lifestyles. In Bdellovibrio bacteriovorus HD100, predation ability is controlled by Bd0742 (DgcB) and its deletion led to Bdellovibrio growing as a Host-Independent (HI) strain that had lost predation ability. During prolonged co-incubation of this mutant with E. coli S17-1, Δ bd0742 suppressor strains arose that could lyse the prey cells. My project built on this work by co-culturing and screening the predation ability of the HI B. bacteriovorus Δ bd0742 mutant strain on a wide range of Gram- negative bacteria including human pathogens. Genomic changes were identified in Δ bd0742 suppressor strains, arising on E. coli prey, detecting in which gene the suppressor mutation lies, and the effect of these suppressor point mutations on levels of c-di-GMP production was also assayed. Co-culture of HI B. bacteriovorus Δbd0742 mutant strain in liquid with different human pathogens and non-pathogenic prey cells showed that this strain was originally unable to lyse all different types of prey cells but that suppressors could arise on some types of prey: E. coli S17-1 and A. baumannii but not on others including Salmonella typhimurium, Serratia marcescens and Pseudomonas putida. Studying the genome sequences of the all Δ bd0742 suppressor strains revealed that there were point mutations in bd3766 (dgcD) which encodes another, previously cryptic, diguanylyl cyclase gene. Furthermore, in some strains there was separate point mutation in bd0134 (askα), and in all strains mutations in bd0467 transposase homology gene which were later found to be due to natural variation. The point mutations in bd3766 occur in bases coding for the coiled coil region and transmembrane domain leading to the proposal that these caused constitutive dimerization of Bd3766 and enhanced Bd3766 activity in the absence of any other regulator protein activity. This was backed up by E.coli swimming assays which indicated a higher level of c-di-GMP inhibiting swimming when the bd3766 suppressor gene alleles were expressed in E.coli on swim plates versus wild type bd3766. Gene transfer and predation ability tests of Δ bd0742 mutant strains showed that the point mutation in bd3766 was the real cause of suppression of the “non- predatory in liquid culture” phenotype of the HI B. bacteriovorus Δ bd0742 mutant strain. Additional to that, despite the suppressor point mutations in Bd3766 producing more c-di-GMP than wild type Bd3766 but, they still could not restore plaque formation on plates, only in liquid predation, on E. coli S17-1 and A. baumannii prey. Finally testing function of some point mutations, found in suppressor mutant genomes, in the DAP synthesis pathway gene, (bd0134), led to the finding that over expression of bd0134 restored plaque formation on agar plates to the suppressor strains. My thesis project (leading from testing bd0134 suppressor studies) also investigated predatory roles of some further genes involved in cell wall synthesis such as m-DAP/Lysine synthesis pathway genes. This study also found that CpoB, a protein that has an important role in cell wall synthesis regulation, during division, in non-predatory bacteria; is also expressed upon prey during the predatory lifecycle. Concordant with this, deletion studies of cpoB suggested that is essential for both HD and HI lifestyles.